Diseño geométrico de la vía Arenillas – intersección ingreso La Cuca, cantón Arenillas - Navarro Cangas, Erick Leandro (Machala: Universidad Técnica de Machala, 2023)
This project aims to solve the need that arises on the road that connects Arenillas city with the entrance to the La Cuca parish. Through a field study it can be confirmed that the lack of road infrastructure that exists in this area affects the socioeconomic development of the population. According to the analysis of the road, a visual inspection was carried out in which it was found that there is an irregularity in the road, this constantly affects agriculture, since in wintertime access to the area is made with greater difficulty. For the geometric development that was carried out on the road, a topographic survey was carried out with an RTK type, a vehicle capacity study using the manual vehicle counting methodology to determine the volume of traffic. The tests that were carried out were the limits of Atterberg, granulometry, Proctor and CBR. This helped us determine the type of soil that is present on the road. The results gave us that a clayey silt soil is present with a resistance that characterizes the subgrade. as very bad, this indicates that soil improvement must be carried out. To carry out this study, the Civil 3D tool was used, with the purpose of obtaining the geometric design of the road and thus determining the cut and fill cubing. In addition, the quantities of material of the road structure that consists of the subgrade, subbase, base and rolling surface, in this way the respective work schedule was carried out.
Afecta al desarrollo socioeconómico de la población. Conforme el análisis de la vía se realizó una inspección visual en la cual se pudo constatar que existe una irregularidad en la vía, esto afecta de manera constante a la agricultura, ya que en tiempo invernal el acceso a la zona se lo realiza con mayor dificultad. Para el desarrollo geométrico que se realizó en la carretera se hizo un levantamiento topográfico con un equipo RTK, un estudio de aforo vehicular mediante la metodología del conteo vehicular manual para determinar el volumen de tráfico. Los ensayos que se realizó fue los límites de Atterberg, granulometría, Proctor y CBR esto nos ayudó a determinar el tipo de suelo que se presenta en la vía sus resultados nos dieron que se presenta un suelo limo arcilloso con una resistencia que caracteriza a la subrasante como muy mala, esto indica que se debe realizar un mejoramiento de suelo. Para la realización de este estudio se utilizó el software Civil 3D, con la finalidad de obtener el diseño geométrico de la vía y asi determinar la cubicación de corte y relleno. Además, las cantidades de material de la estructura vial que consiste en la subrasante, subbase, base y carpeta de rodadura, de esta manera se realizó la respectiva programación de obra.
Keywords: DISEÑO GEOMETRICO; CARRETERA; AFORO VEHICULAR; TRAZADO GEOMETRICO